On the food of northern krill Meganyctiphanes norvegica in relation to its vertical distribution - Lass, S; Tarling, G; Virtue, P; Matthews, J; Mayzaud, P; Buchholz, F (Marine Ecology Progress Series, 2001)
The feeding behaviour of northern krill (Meganyctiphanes norvegica) was studied inpopulations from the Clyde Sea and the Kattegat during summer and winter. The food spectrum in thestomachs was analysed using traditional taxonomic methods and biochemical techniques. The verticalmigration behaviour of krill was monitored through a 30 h series of net samples, whilst the trophic environmentwas characterised through accompanying quantitative analyses on the depth distributionand biomass of copepods and phytoplankton. Krill was found to be more carnivorous in the Kattegatthan in the Clyde Sea, which correlated with the higher ratio of copepod to phytoplankton biomassfound in the Kattegat compared with the Clyde Sea. High levels of fatty alcohols and other lipid markersin the stomach contents of Kattegat krill were also indicative of a carnivorous diet. Other foodsources included detritus, terrestrial material and other euphausiids, underlining the opportunistic natureof northern krill in its choice of prey items. Analyses of stomach and intestinal fullness over a dielcycle showed significant variations with time in the Clyde Sea but not in the Kattegat. However, a dielcycle in the rate of ingestion was evident at both locations when comparing the copepod mandibles inthe stomachs to the distribution of copepods in the environment. The fact that deep-living Calanus wasnot a major prey item suggested that there was little feeding activity during the daytime, when the krilloccupied the deeper layers. Instead, the majority of mandibles were from species that were dominantin the upper layers, e.g. the genera Temora and Pseudocalanus. The fact that krill caught in the daytimecontained the same relative composition of mandibles in the stomach as those caught at night isprobably explained by a cessation in daytime feeding activity and retention of the mandibles from thenight before. It is proposed that krill in the Clyde Sea area and the Kattegat show a diel rhythm in feedingactivity that is believed to be an adaptive response to minimising predation risk.